Production of Napoli salami from some swine autochthonous genetic types. IV. Characteristics of the mycoflora - Marziano F.; Morra A.; Nanni B.; Fornataro D.; Palazzo M.; Matassino D. (Tradition and innovation in Mediterranean pig production, 2000)
Forty-six salami, distinct by genetic type, sex and plants of seasoning were examined to show eventual relationships among these factors and the food quality characteristics, rate of fungal colonization and species of moulds grown on them. Yeast was not considered for this study. Rate of colonization was much higher in salami seasoned at Angri (SA) than in those seasoned at Morcone (BN). On the contrary, neither the genetic type nor the sex of swine influenced the rate of fungal colonization of the salami. The species of fungi most frequently isolated in salami seasoned both at Angri and Morcone, were P. aurantiogriseum and P. nalgiovense. The occurrence of P. brevicompactum, P. griseofulvum, P. implicatum and P. italicum was low. Only rarely fungi of other genera (Fusarium, Trichoderma, Cladosporium, Mucor, Aureobasidium) were isolated. A rather high probability that food quality characteristics of the salami depend on high level of fungal colonization was found.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)